Rethinking Asset Recovery in Indonesia: The Urgency of Non-Conviction Based Forfeiture (NCBAF) within a Substantive Justice Framework - Irdanul Achyar (Indonesian Journal Publisher, 2026)
This article critically examines the urgency of reforming the asset recovery policy and the restitution of state financial losses in corruption cases in Indonesia. Although asset recovery occupies a central position in the anti-corruption regime, the current positive legal framework remains fragmentary and incomprehensive, particularly due to a legal vacuum (vacuum of law) regarding a specific asset forfeiture law. At the practical level, the application of the safekeeping institution mechanism, which is rooted in civil law, into the realm of criminal proceedings has triggered structural disharmony between legal regimes. This condition undermines the principles of due process of law, the protection of property rights, and legal certainty, while also creating loopholes for abuse of power and the criminalization of corporations. Furthermore, the discourse on adopting the Non-Conviction Based Asset Forfeiture (NCBAF) instrument brings about a sharp intersection between the efficiency of law enforcement and the protection of constitutional rights. Through a normative legal research method combined with a socio-legal approach, this study analyzes statutory instruments, legal doctrines, and law enforcement practices to identify legal loopholes and disharmony within the national asset recovery system. The research findings indicate that the current legal construction is fraught with normative conflicts, regulatory vacuums, and weak institutional accountability, which in turn reduces the effectiveness and legitimacy of law enforcement. This article argues that asset recovery must be reconstructed so that it does not merely operate as a technical law enforcement instrument, but is repositioned into a paradigm of substantive justice. The research proposes a legal reform model that emphasizes the acceleration of NCBAF legislation enactment, accompanied by strict procedural safeguards, clear demarcation of institutional authority, and the practical integration of restorative and redistributive justice values. This research contributes to the discourse on asset recovery by offering a novelty perspective that elaborates on anti-corruption efforts through the rule of law principle and a justice-oriented governance approach.